Analysis of Factors Influencing the Acceptance of Riliv Application Using UTAUT2 - Abrila Fatzali; Anita Wulansari; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
The rapid growth of digital technologies has enabled the emergence of online counseling services as alternative solutions for addressing mental health issues. Riliv is one such platform that provides digital psychological support through professional consultations, guided meditation, and journaling features. However, few studies have applied the UTAUT2 model to examine user acceptance of such platforms within the Indonesian context. This research addresses that gap by extending the UTAUT2 model with three additional constructs: e-health literacy, privacy concern, and trust. A quantitative approach was employed through a structured survey of 400 participants, with data analyzed using SEM-PLS. The findings indicate that performance expectancy, effort expectancy, social influence, facilitating conditions, privacy concern, and trust significantly influence users’ behavioral intention to adopt Riliv. Interestingly, price value and e-health literacy were found to be insignificant, suggesting that users may place greater emphasis on emotional safety and social dynamics than on financial or informational aspects when choosing mental health platforms. Moreover, while performance expectancy is often a key predictor in technology adoption, it may be less dominant in emotionally driven contexts such as mental health. The extended UTAUT2 model proved effective in predicting user acceptance, confirming its relevance for evaluating digital mental health services in Indonesia. These insights emphasize the importance of building trust, ensuring privacy, and fostering a socially supportive, user-friendly experience. Collaboration between developers and mental health professionals is crucial to aligning technological design with user expectations and emotional needs.